1992
DOI: 10.1037/0033-2909.112.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Primacy of wholistic processing and global/local paradigm: A critical review.

Abstract: The question of whether perception is analytic or wholistic is an enduring issue in psychology. The global-precedence hypothesis, considered by many as a modern version of the Gestaltist claim about the perceptual primacy of wholes, has generated a large body of research, but the debate still remains very active. This article reviews the research within the global/local paradigm, and critically analyzes the assumptions underlying this paradigm. The extent to which this line of research contributes to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
621
3
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 651 publications
(668 citation statements)
references
References 89 publications
29
621
3
8
Order By: Relevance
“…It is already known that in adults, many parameters affect the global advantage [see Kimchi, 1992], including the length of the exposure duration and the spacing between and the number of local elements, and are especially relevant to differences in the developmental findings. In some adult studies, asymmetrical global-tolocal interference has only been observed under very short exposure durations [Paquet & Merikle, 1984] and when there are many local elements close together that generate good exemplars of the global figure [Kimchi, 1998;Martin, 1979;Navon, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that in adults, many parameters affect the global advantage [see Kimchi, 1992], including the length of the exposure duration and the spacing between and the number of local elements, and are especially relevant to differences in the developmental findings. In some adult studies, asymmetrical global-tolocal interference has only been observed under very short exposure durations [Paquet & Merikle, 1984] and when there are many local elements close together that generate good exemplars of the global figure [Kimchi, 1998;Martin, 1979;Navon, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of empirical evidence points toward a fixed integration process that starts with the coarse information (contained in LSFs) and then moves on to the fine information (contained in HSFs), similar to object or form perception in general (e.g. Hughes, Face Perception 18 Fendrich & Reuter-Lorentz, 1990;Hughes, Nozawa & Kitterle, 1996;Kimchi, 1992;Navon, 1977;Sanocki, 1993) . However, some empirical evidence has also indicated processing can be flexible, as processing is sometimes coarse to fine, while others it is fine to coarse.…”
Section: When Are Sfs Selected? the Microgenetic Approachmentioning
confidence: 99%
“…In a related vein, a phenomenon called global-to-local has been thoroughly studied since Navon's (1977) influential research (e.g., Kimchi, 1992, for a review; see also Hughes, Nozawa & Kitterle, 1996;Lamb & Yund, 1996a, 1996bPaquet & Merikle, 1988;Robertson, 1996; among many others). Navon used hierarchical letters similar to those presented in Fig.…”
Section: Coarse-to-fine Recognitionmentioning
confidence: 99%